1973
DOI: 10.1111/j.1399-0004.1973.tb01121.x
|View full text |Cite
|
Sign up to set email alerts
|

A problem in diagnosis of primary versus secondary microcephaly

Abstract: Twenty‐six primary and 21 secondary microcephalics were compared on the criteria of family and birth factors and clinical examinations. The two groups were similar in respect to their birthweights and parental ages at the time of birth. The group characteristics of primary microcrphalics that appear to be useful in distinguishing them from secondary cases are: (1) consanguinity in two of 13 families, (2) significantly increased number (18.9%) of pregnancy losses, (3) almost normal conditions of gestation, deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
23
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 5 publications
2
23
0
Order By: Relevance
“…These results are in concordance with the findings of Qazi and Reed (1973). In contrast the data of the pathogenetic classification indicated that as a whole and as compared with IMC, participants in the MMC group showed a higher mean IQ, and a lower prevalence of profound LD or epilepsy.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…These results are in concordance with the findings of Qazi and Reed (1973). In contrast the data of the pathogenetic classification indicated that as a whole and as compared with IMC, participants in the MMC group showed a higher mean IQ, and a lower prevalence of profound LD or epilepsy.…”
Section: Discussionsupporting
confidence: 77%
“…However, this result needs further investigation to determine whether it is a general characteristic of MC or a chance effect. In most studies (Qazi and Reed 1973, Opitz and Holt 1990, Scheffer et al 1992, MC is usually viewed as primary (when environmental factors are excluded) or secondary. Given the heterogeneous nature of a sign which comprises such a diverse group of disorders, marked variations would be expected.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…24 The second study found that epilepsy was 4 times more common in postnatal onset microcephaly. 25 Microcephaly is a significant risk factor for medically refractory epilepsy (MRE). [26][27][28] In a Class III study of 30 children, microcephaly was found in 58% of those with MRE compared to 2% in whom seizures were controlled (odds ratio 67.67; p Ͻ 0.001).…”
mentioning
confidence: 99%